KETERANGAN AHLI VISUM ET REPERTUM DALAM PEMBUKTIAN PERKARA KEKERASAN DALAM RUMAH TANGGA - Salim, Kartika Agus (Universitas Kapuas, 2025)
Based on Article 183 of Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP), it can be concluded that before a judge imposes a crime on a suspect/defendant, the judge needs two pieces of evidence. This evidence serves to strengthen the judge's confidence in the criminal act committed by the suspect/defendant. However, at the conference stage at the Sintang District Court Session, the expert witness who was requested was not present and at the conference the one who read the statement was the Public Prosecutor, so according to the researcher the expert witness was absent but the conference continued and in the end the expert witness' statement was confirmed even though he was not present in person. offline but online. Therefore, the author was interested in conducting a study entitled